ANALISIS STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 3 PADA MATA PELAJARAN BAHASA INDONESIA DI SD SEMESTA BILINGUAL SCHOOL - Safira Yogi Fahdiana; Riris Setyo Sundari; Siti Patonah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher strategies in improving third-grade student’s learning motivation in Indonesia language subjects at Semesta Bilingual School Elementary School. This study uses a qualitative approach with a case study design. The research subjects include the principal, third-grade teachers, and third-grade students. Data collection techniques were carried out throught interviews, observation, and questionnaires. Data analysis used descriptive qualitative techniques throught the stages of data reduction, data presentation, and drawing conclusions. The results show that teacher strategies in improving student learning motivation are carried out through communicative and fun learning, the use of varied methods, and the provision of rewards in the form of points, praise, and symbols of appreciation. In addition, teachers also create a conducive learning atmosphere and adjust the use of Indonesian and English in learning. These strategies are able to increase student activity, enthusiasm, and involvement in learning Indonesia in a bilingual environment. Supporting factors include the availability of learning resources and environmental support. Meanwhile, the challenge is the dominance of the use of English in school. Thus, teacher strategies play an important role in improving student learning motivation.